Effect of Hydrogen Peroxide (H2O2) on Different Levels of Water Availability on Vegetative Growth of Soybean Plants [Glycine max (L.) Merr.] Argomulyo Varieties - Ika Shintya; Sri Widodo Agung Suedy; Endah Dwi Hastuti (Bioscience, 2020)
The soybean [Glycine max (L.) Merr.] is one of the important sources of vegetable protein and agricultural commodities in Indonesia, but its productivity is uncertain due to various factors, one of which is the availability of water. Low water availability in the growing environment can cause soybean plants to suffer from drought stress. Giving hydrogen peroxide to plants experiencing drought stress in optimum concentration can increase the plant's oxidative defense system. This study aims to determine the effect of treatment on the vegetative growth of Argomulyo variety soybean plants. The study used a factorial completely randomized design (CRD) design with 2x4 treatment and 5 replications. The parameters observed were plant height, number of leaves, leaf area, and fresh dry weight of the root canopy at the level of water availability 100% and 35% field capacity by spraying hydrogen peroxide concentrations of 0 mM, 0.5 mM, 1 mM, and 2 mM. The results were analyzed by ANOVA and DMRT test with a significance level of 0.05. The level of water availability influences plant height, number of leaves, leaf area, and fresh dry weight of the root canopy. The results show a 100% water availability level has a higher yield. Keywords: soybean, hydrogen peroxide, stress, growth